Abordagens plurais das línguas no ensino fundamental: experiência piloto com pré-adolescentes de uma escola pública de Belo Horizonte - Érica Sarsur Câmara (2020)
This work is in the field of didactics of plurilingualism and is guided by pluralistic approaches to the teaching of languages and cultures, specifically, the awakening to languages (éveil aux langues) and the intercomprehension between Romanic languages. Pluralistic approaches contribute to the development of apprentices in the fields of knowledge, attitudes and skills, favouring awareness of their linguistic reality and expanding openness towards otherness. The aim of this research was to investigate the effects of pluralistic approaches on the integral formation of pre-adolescents from disadvantaged socioeconomic backgrounds. To this end, a pilot project was prepared, entitled “Reading the world”, based on pluralistic approaches, for the public of the 6th year of middle school in a public school located on the border of a subnormal agglomerate in Belo Horizonte. The data analysed in this action-research comes from two questionnaires, one answered by the students and the other by the teachers; student production in classroom activities; semi-structured interviews, carried out with groups of students; and the teacher's reflective diary. These data were analysed according to the content analysis model, with the support of thematic analysis and enunciation. Three types of analysis were performed. The first focuses on the benefits of the pilot project for the integral formation of students and points out positive results and the awareness, by students, of the elements that influence their learning process. The second is organized on the basis of eleven categories, organized in three fields: knowledges, attitudes and skills. The results point to positive changes in most of the students who participated in the project. Complex issues that interfere with students' behaviour at school were also identified, which highlights the importance of establishing a closer dialogue between the school and the institutions of the city's Child and Adolescent Protection Network. The third type of analysis was dedicated to the commented verification of the adequacy of the proposed activities to the context of experimentation and its relationship with the set of resource descriptors presented in the framework of reference for pluralistic approaches to languages and cultures (FREPA). The activities proved to be adequate, and there are different ways of deepening and improving the way of presenting and conducting them. The work brought practical contributions to the field of didactics of plurilingualism, as it presents a structured and commented device, which can be used in other school contexts. It also brought theoretical contributions, insofar as it proposes the inclusion of two sections of resource descriptors in the framework of reference for pluralistic approaches to languages and cultures (FREPA): general and world knowledge (field of knowledge); knowing how to mediate knowledge (field of skills). This work corroborates the positive effects of pluralistic approaches for apprentices pointed out by previous works carried out in several countries and presents itself as a contribution to strengthen this field of studies in the Brazilian context.